Calculation of evaporative-radiant cooling of recycled water in summer air-conditioning systems - Usmonov N. O.; Hazratov A. G.; Usmonov J. Y. (E3S Web of Conferences, 2023)
The paper describes the calculation of evaporative-radiant cooling of recycled water in summer air-conditioning systems. A differential equation for the heat balance of water flowing down an inclined plane is derived. One possible way of increasing the efficiency of air conditioning systems based on cooling water by adiabatic evaporation in the air flow is using night-time evaporative cooling of the water, followed by daytime cooling in insulated storage tanks. The temperature of the water chilled in this way is 3-4 ° lower than the temperature of the water chilled during the day, and the final water temperature is close to the saturation temperature of the outside air. The equations for calculating mass transfer coefficients, radiation, and heat transfer coefficients of an insulated bottom of an evaporative-radiant water-cooling unit are given. Based on the Mathcad program and the result of the calculation, the dependence of the final water temperature on the initial water temperature is obtained. As a result of the calculation, the specific heat capacity of the evaporative radiant water-cooling unit for the production of free cooling is determined.